Biokinematic Determinants As An Indicator For The Selection Of Junior Clubs In Dhi Qar Province In Volleyball - Malka, Tuqa Adnan; Prof, Prof; Mushgel, Nasrallah radhi (Journal of Neonatal Surgery, 2025)
The study aimed to identify the most important biokinematic determinants and physical measurements for the selection of junior players in Dhi Qar volleyball clubs for the 2024-2025 sports season. And determine a model for the selection of players according to the biokinematic and physical determinants of young players in the clubs of Dhi Qar province in volleyball for the sports season 2024-2025 using the method of factor analysisThe researcher used the descriptive approach in a survey method and correlational relations, and represented the research community with players clubs in Dhi Qar volleyball province, numbering (98) players and representing clubs (victory - Al-Jabayesh - Al-Shatrah - Souk Al-Shuyoukh - Nasiriyah - confirmed - Marshes) The research sample has been chosen in a deliberate way after excluding (free player - prepared player) to be (72) players who can perform skills (wavy transmission of jumping - receiving the transmission from the bottom - overwhelming beating Qatar), and the researcher used means and tools And appropriate devices in achieving the objectives of the research and concluded the researcher a set of conclusions, the most important , the extraction of (five) factors through factor analysis of biokinematic variables of the skill of wavy transmission of jumping volleyball has neglected some factors for not meeting the conditions for accepting factors.